Developing drugs in cancer-related bone pain. (November 2017) - Lucchesi, Maurizio; Lanzetta, Gaetano; Antonuzzo, Andrea; Rozzi, Antonio; Sardi, Iacopo; Favre, Claudio; Ripamonti, Carla Ida; Santini, Daniele; Armento, Grazia
Highlights: About 75% of patients with bone involvement is interested by pain. Cancer-related bone pain has both a nociceptive and a neuropathic component. Cancer-related bone pain could be treated with analgesics drugs, or prevented with "bone therapy". Moreover, new biological drugs are in development for this topic. Abstract: Introduction: Cancer-related bone pain is a frequent and important key problem for metastatic patients that may reduce quality of life, with related limitations in daily activities and morbidity. Often traditional approach to pain may fail given the complex pathophysiology of this phenomenon. Methods: The aim of this review is to describe promising therapies for cancer-related bone pain, from the pathophysiology to the clinical trials currently ongoing. Moreover, any new evidence for better approach to cancer-related bone pain with the traditional drugs is also considered. Conclusions: In clinical practice opioids remain the most important pharmacologic treatment for severe pain related to bone cancer. Regard developing drugs, anti-NGF and anti-TrkA are the most investigated new drug in this setting, but a future role in clinical practice is still uncertain.